Effects of acute hypoxia on gene expression and physiology in Atlantic cod (Gadus morhua) after chronic dietary exposure to an organophosphate pesticide - Cho, Ki Chung (Nord universitet, 2020)
Masteroppgave i havbruk og akvakultur - Nord universitet 2020